An ethnographic study of communication with HIV-infected children at Rumah Cemara - Yustikasari Yustikasari; Atwar Bajari; Ponpon Idjradinata; Eni Maryani (Jurnal Kajian Komunikasi, 2022)
This study examines the ethnography studies of communication with HIV-infected children at Rumah Cemara Bandung by reviewing the elements of communication components. This research uses a qualitative approach with an ethnographic type of communication study. The research subjects were children infected with HIV in Bandung who was selected using the purposive method. Data were obtained through in-depth interviews, participatory observation, document analysis, and literature study. The results revealed that the genre in the communication component of children infected with HIV at Rumah Cemara was seen in the delivery of problems, namely the presence of viral infections in children. The setting that occurs in the communication component is carried out at the child's home/residence and Rumah Cemara as a community location and Klinik Teratai, Hasan Sadikin Hospital, Bandung. Children use Indonesian and Sundanese as their daily languages. All HIV-infected children are infected with the virus because it is transmitted from their parents, namely the mother, and the mother is infected with HIV from her husband. Conversations that are usually carried out by informants when meeting at Klinik Teratai, Rumah Cemara, and at home are usually related to conditions of health development, children's adherence to taking anti-retroviral drugs, and mental and social development of children with messages of mutual encouragement and support as well as instilling a sense of optimism. Psychologically among People With HIV/AIDS (ODHA). The non-verbal language that children do in the form of silence; smiles; a nod of the head; shaking of the head, and laughing out loud.